From here to eternity - Zinnemann, Fred 1907-; Adler, Buddy 1906-1960; Taradash, Daniel 1913-; Jones, James 1921-1977 (Columbia Pictures, 1963)
In 1941, at a peacetime army camp in Hawaii, a captain's wife and a career soldier fall in love, while a private is cruelly punished for refusing to box on his unit's team.